Capacity Building Untuk Optimalisasi Tata Kelola Poskestren Di Pondok Pesantren Burhanul Hidayah - Satriya - Wijaya; Novera Herdiani (STIKES Yayasan RS.Dr.Soetomo, 2026)
In 2024, this Islamic Boarding School had around 700 students, with the majority living in the boarding school (mukim), around 380 people. From the results of observations that have been carried out, several problems were found regarding personal hygiene, environmental sanitation, PHBS, poor food and nutrition processing methods, waste management and processing, overload of student capacity in each room, inadequate condition of student rooms, and suboptimal management of the Poskestren. This community service program aims to improve the capacity and quality of Poskestren managers, both in terms of managerial skills and relevant medical knowledge, so that Poskestren can be managed better and can provide more optimal health services to the residents of the Islamic boarding school. The methods or steps for implementing this community service include: (1)Identifying problems, knowledge, and skills of students/residents of Islamic boarding schools regarding basic health services, as well as the management and operations of health posts (Poskestren). (2)Intervening to improve students' knowledge and skills. (3)The expected outcomes of this intervention. The results of this community service activity in the basic health services training showed an increase in participant understanding, from 48.57% to 82.14%. Meanwhile, in the community health post management training, participant understanding increased from 84.09% to 96.81%. This community service activity is that it aims to build the capacity of individual students to be able to carry out basic health services and implement good management or governance of Islamic boarding schools.